Heteragrion calafatiensis (Odonata: Heteragrionidae) sp. nov. from Northern Brazil - Mendoza-Penagos, Cristian Camilo; Juen, Leandro; Vilela, Diogo Silva [UNESP] (Magnolia Press, 2022)
The Neotropical genus Heteragrion Selys, 1862 is the second most speciose among the Neotropical Zygoptera. However, most of its species are poorly known regarding their biology, distribution, and taxonomy, especially those from undersampled areas like Northern Brazil. Here we describe Heteragrion calafatiensis sp. nov. from the coastal environments of the Brazilian Amazon of Par state (Holotype , Brazil, Par, municipality of Magalhes Barata, near the Marapanim River, (-0.863291, -47.668058, 20 m, 26.ix.2021), C.C. Mendoza-Penagos leg, in UFPA). This is the nineth Heteragrion species recorded for the Northern region of Brazil. The new species can be separated from congeners by cercal morphology and thoracic coloration pattern.